Outward foreign direct investment and economic growth in China: evidence from asymmetric ARDL approach - Ali, Usman; Shan, Wei; Wang, Jian-Jun; Amin, Azka (Journal of Business Economics and Management, 2018)
The current study explored the dynamics between economic growth and overseas investment, using time series annual data from China. For empirical analysis, we utilized asymmetric ARDL technique, which documents the potential asymmetric effects of outward foreign direct investment on economic growth in both the long run and short run. The empirical results suggest that ignoring the intrinsic asymmetries may conceal the true information about the equilibrium relationship among the variables and thus lead to misleading results. Particularly, the findings revealed that economic growth in China responds positively but differently to an increase and decrease in its overseas investment. The empirical evidence obtained through asymmetric model seemed to be superior to that of symmetric model and thus leads to more efficient policymaking to achieve sustainable economic development. Our study contributes to the existing literature by providing new insights on the outward foreign direct investment-led growth hypothesis. The findings suggest that firms investing abroad can bring source country benefits by securing access to key input factors and accessing advanced foreign technology.